Prevalence and Factors Associated with Lower Reproductive Tract Infections Among Married Women Aged 18–49 in Dong Phu Commune, Long Ho District, Vinh Long Province, 2018 - Nguyen Thi Ngoc, Bich; Doan Thi Thuy, Duong; EVansluong David Vinh, Quang (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2020)
Objective: To understand the patterns and associated factors of reproductive tract infections among married women aged from 18 to 49 in Dong Phu Commune, Long Ho District, Vinh Long Province in 2018. Methods: A cross-sectional study was conducted with 420 married women aged 18-49 by systematic sampling. Participants were invited to have a gynecological examination and answer a questionnaire at Dong Phu commune health station. Results: Of 420 women, 43.6% had lower reproductive tract infections, and those who had bacterial vaginosis accounted for 36.2%, vaginal candidiasis accounted for 9.3%, and Trichomonas vaginalis accounted for 1.0%. Factors associated with lower reproductive tract infections, including occupation, abortion history, and adherence to treatment, were found in this study. Conclusion: The prevalence of genital tract infections (by one of three types) is 43.6%. It is necessary to enhance counseling services and behavior change communication for women who work as peasants, gardeners, fisherwomen, housewives; and to improve the quality of abortion services and the awareness of treatment adherence.